Quantitative Profiling of Long-Chain Bases by Mass Tagging and Parallel Reaction Monitoring. - Christer S Ejsing; Mesut Bilgin; Andreu Fabregat (PLoS ONE)
Long-chain bases (LCBs) are both intermediates in sphingolipid metabolism and potent signaling molecules that control cellular processes. To understand how regulation of sphingolipid metabolism and levels of individual LCB species impinge upon physiological and pathophysiological processes requires sensitive and specific assays for monitoring these molecules. Here we describe a shotgun lipidomics method for quantitative profiling of LCB molecules. The method employs a "mass-tag" strategy where LCBs are chemically derivatized with deuterated methyliodide (CD3I) to produce trimethylated derivatives having a positively charged quaternary amine group. This chemical derivatization minimizes unwanted in-source fragmentation of LCB analytes and prompts a characteristic trimethylaminium fragment ion that enables sensitive and quantitative profiling of LCB molecules by parallel reaction monitoring on a hybrid quadrupole time-of-flight mass spectrometer. Notably, the strategy provides, for the first time, a routine for monitoring endogenous 3-ketosphinganine molecules and distinguishing them from more abundant isomeric sphingosine molecules. To demonstrate the efficacy of the methodology we report an in-depth characterization of the LCB composition of yeast mutants with defective sphingolipid metabolism and the absolute levels of LCBs in mammalian cells. The strategy is generic, applicable to other types of mass spectrometers and can readily be applied as an additional routine in workflows for global lipidome quantification and for functional studies of sphingolipid metabolism.